Discovery of the Naturally Occurring Pure CaTiO3 Cubic Perovskite from Tazheran Massif - Sun, Jing; Liu, Jin; Liu, Fuyang; Sklyarov, Eugene; Mitchell, Ross (Earth and Planetary Science, 2024)
As the parent compound of the perovskite-structured family and an analogue of davemaoite CaSiO3 in Earth’s lower mantle, CaTiO3 perovskite is widely used in electronic ceramic materials, immobilizing radioactive waste, and geosciences. Here we report the discovery of a natural pure CaTiO3 perovskite-C in calc-silicate veins in brucite marble in the Tazheran Massif, Russia. The mean composition of perovskite-C is 97 wt% total CaO and TiO2, and minor impurities of Na, Al, and Zr, yielding the chemical formula CaTi0.97Al0.01Na0.01Zr0.01O3. The cubic crystal structure—Pm3m, Z = 1: a = 3.8301 Å, V = 56.19 (2) Å3 (ρ = 4.019 g/cm3) has been refined to R1 = 0.0451. Compared with the cubic perovskite discovered in Israel, the cubic perovskite discovered in this study is very pure in Ca and Ti. The naturally occurring perovskite-C from Tazheran implies that the host skarn might have experienced high-temperature (> 1247–1374 °C) metamorphism and/or metasomatism at an early stage. Moreover, the discovery of natural perovskite-C also draws attention to considering crystal-structure-related matrix effects in the future of in situ U-Pb geochronology, especially using Tazh international perovskite standards.